Leuconostoc mesenteroides subsp. mesenteroides SJRP55 reduces Listeria monocytogenes growth and impacts on fatty acids profile and conjugated linoleic acid content in fermented cream - Borges, Danielle Oliveira [UNESP]; Matsuo, Mariana Mitiko; Bogsan, Cristina S. Bittencourt; Silva, Tatiane Ferreira da [UNESP]; Casarotti, Sabrina Neves; Penna, Ana Lúcia Barretto [UNESP] (Elsevier, 2019)
The effect of Ln. mesenteroides subsp. mesenteroids SJRP55 on the fatty acid profile, on the content of bioactive unsaturated fatty acids, on the inhibition Listeria monocytogenes and on bacterial viability in fermented cream were evaluated. Fermented cream treatments were produced using Lactococcus spp. alone (T1), in co-culture with L. monocytogenes (T2) or Ln. mesenteroides subsp. mesenteroids SJRP55 (T3), and with both microorganisms simultaneously (T4), followed by 28 day-storage. Ln. mesenteroides subsp. mesenteroides SJRP55 caused a reduction on L. monocytogenes population and had distinguished effect on fatty acid profile, causing a reduction on the monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA), as well as an increase in saturated fatty acids (SFA), only on the first day of storage. Fermentation resulted in increased conjugated linoleic acid (CLA) and decreased α-linolenic (ALA) and oleic (OA) acids contents. The cream fermented by Lactococcus spp. and Ln. mesenteroides subsp. mesenteroides SJRP55 showed potential functional properties in CLA content. The treatments were characterized according to their bioactive unsaturated fatty acids using the principal component analysis (PCA). The first principal component (70.25%) was explained by OA and CLA, and the second principal component (25.79%) was explained by ALA, totaling 96.44%. Ln. mesenteroides subsp. mesenteroides SJRP55 improved the functional properties and safety of fermented cream.
Keywords: Antimicrobial activity; Conjugated linoleic acid; Fermented dairy product